Creditor Control Rights, Corporate Governance, and Firm Value - Nini, Greg; Smith, David C.; Sufi, Amir (Review of Financial Studies, 2012)
We provide evidence that creditors play an active role in the governance of corporations well outside of payment default states. By examining the Securities and Exchange Commission's filings of all U.S. nonfinancial firms from 1996 through 2008, we document that, in any given year, between 10% and 20% of firms report being in violation of a financial covenant in a credit agreement. We show that violations are followed immediately by a decline in acquisitions and capital expenditures, a sharp reduction in leverage and shareholder payouts, and an increase in CEO turnover. The changes in the investment and financing behavior of violating firms coincide with amended credit agreements that contain stronger restrictions on firm decision-making; changes in the management of violating firms suggest that creditors also exert informal influence on corporate governance. Finally, we show that firm operating and stock price performance improve post-violation. We conclude that actions taken by creditors increase the value of the average violating firm. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.